Correlation between Cup Ratio and Optic Nerve Disc with High Myopia - Nur Shani Meida; Ahmad Ikliluddin; Yunani Setyandriana; Nadia Dina Ayu (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2021)
High myopia is one of the risk factors for glaucoma, which is often accompanied by abnormalities in the fundus due to excessive stretching. The object of the study is to determine correlation between cup ratio and optic nerve disc with high myopia. This is a non-experimental research, analytic observational  with cross-sectional study design. The subjects were patients with myopia with more than – 6.00 diopters at the Kebumen Eye Center Clinic and Purbowangi Gombong Hospital. Data collection was carried out in January - August 2019. The respondents  were 30 people, consisting of 14 men (46.7%), 16 women (53.3%), with an average age of 33.07 ± 18.04 years. Mean refraction of right eye (OD / Ocular Dextra) were -10.72 ± 4.82 diopters and left eye (OS / Ocular Sinistra) were -10.27 ± 4.52 diopters. The results of the correlation test using Spearman Test showed that there is no significant correlation (OD p = 0.115, OS p = 0.118) between the cup ratio and optic nerve disk with high myopia. It conclude that there is no significant correlation between cup ratio and optic nerve disc with high myopia.